Pengaturan Kendaraan Modifikasi Untuk Difabel dalam Pengoperasian Lalu Lintas dalam Prespektif Hukum Transportasi - Dywananda, Auliya Cistaraja Javier; Chumaida, Zahry Vandawati (Media Iuris, 2024)
AbstractLaw Number 22 of 2009 concerning Road Traffic and Transportation stipulates that motorized vehicles operating on highways must meet technical and other road requirements as referred to in Article 48 of Law Number 22 of 2009 concerning Road Traffic and Transportation. In the development of motorized vehicles, modifications are often made both for hobbies, work, and others, even to make it easier for persons with disabilities to drive motorized vehicles, modifications to motorized vehicles are carried out which cause changes in type or not to change type. This research is intended to analyze and answer the regulation of modified vehicles used by persons with disabilities on the road. This research approach uses a statutory approach (statute approach) and a conceptual approach (conceptual approach). This type of research data is normative research by examining examining the rules related to disabilities and Law Number 22 of 2009 concerning Road Traffic and TransportationNumber. For this reason, if a modified vehicle is in accordance with Article 6 and Article 64 Government Regulation Number 55 of 2012 concerning Vehicles, it must meet technical and road-worthy requirements. In addition, the operation of motorized vehicles by persons with disabilities that have been modified is permitted as long as they meet the technical and road-worthy requirements and the persons with disabilities have a driving license D in accordance with the provisions of the Road Traffic and Transportation Law Number 22 of 2009.Keywords: Motorized Vehicles; Persons with Disabilities; Motorized Vehicle Modifications. AbstrakUndang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan memberikan pengaturan terhadap kendaraan bermotor yang dioperasikan di jalan raya harus memenuhi syarat teknis dan lain jalan sebagaimana Pasal 48 Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. Dalam perkembangannya terhadap kendaraan bermotor dengan modifikasi yang salah satunya peruntukannya untuk memudahkan para penyandang disabilitas dalam mengendarai kendaraan bermotor, maka dilakukan modifikasi kendaraan bermotor yang menyebabkan perubahan tipe maupun tidak merubah tipe. Penelitian ini dimaksudkan guna menganalisis dan menjawab terhadap pengaturan kendaraan modifikasi yang digunakan oleh para penyandang disabilitas di jalan raya. Pendekatan penelitian ini menggunakan pendekatan undang-undang (statute approach) dan pendekatan konseptual (conceptual approach). Jenis data penelitian ini adalah penelitian normative dengan menelaah aturan yang terkait dengan difabel dan Undang Undang Lalu Lintas Angkutan Jalan Nomor 22 Tahun 2009. Untuk itu apabila kendaraan yang dimodifikasi sesuai Pasal 6 dan Pasal 64 Peraturan Pemerintah Nomor 55 Tahun 2012 tentang Kendaraan maka harus memenuhi persyaratan teknis dan laik jalan. Selain itu Pengoperasian kendaraan bermotor oleh penyandang disabillitas yang sudah dimodifikasi diperbolehkan sepanjang memenuhi persyaratn teknis dan laik jalan serta penyandang disailtas tersebut memiliki SIM D sesuai ketentuan dalam Undang Undang Lalu Lintas Angkutan Jalan Nomor 22 Tahun 2009.Kata Kunci: Kendaraan Bermotor; Penyandang Disabilitas; Modikasi Kendaraan Bermotor.